2021
DOI: 10.1155/2021/5549847
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Antimicrobial Susceptibility Patterns, and Risk Factors Associated with Enterococci among Pediatric Patients at Dessie Referral Hospital, Northeastern Ethiopia

Abstract: Background. Enterococcus species, which is previously considered as medically not important, now becomes one of the leading causes of nosocomial infections. Even though it becomes the most public health concern and emerging multidrug-resistant pathogen, there is no enough data in the study area. Objective. To determine the prevalence, antimicrobial resistance pattern, and associated risk factors of enterococci infection in pediatric patients. Methods. A hospital-based cross-sectional study was conducted from F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
(45 reference statements)
2
12
0
Order By: Relevance
“…This finding was comparable with a study report from Spain (80%) [52], India (82%) [53], Jimma, Ethiopia (89.5%, 80.8%) [25,49], southern Ethiopia (82.5%) [47], and Gondar (75%) [24]. However, it was considerably higher in comparison to other study findings from Dessie, Ethiopia (54.5%) [54], Germany (13.4%) [55], India (10%) [56], and Brazil (57%) [57]. The variations could be related to variances in This was the study's most remarkable finding, and it is a concerning indication of resistance's expanding prevalence.…”
Section: Discussionsupporting
confidence: 85%
“…This finding was comparable with a study report from Spain (80%) [52], India (82%) [53], Jimma, Ethiopia (89.5%, 80.8%) [25,49], southern Ethiopia (82.5%) [47], and Gondar (75%) [24]. However, it was considerably higher in comparison to other study findings from Dessie, Ethiopia (54.5%) [54], Germany (13.4%) [55], India (10%) [56], and Brazil (57%) [57]. The variations could be related to variances in This was the study's most remarkable finding, and it is a concerning indication of resistance's expanding prevalence.…”
Section: Discussionsupporting
confidence: 85%
“…We observed a high proportion of enterococci among infants less than one year old. Other studies reported the same findings and also showed a significant association between pediatrics enterococcal infection and having a history of invasive treatment procedure/chronic illness, admission, or hospitalization [ 24 ]. However, our study did not explore such an association due to the absence of patient clinical data.…”
Section: Discussionsupporting
confidence: 57%
“…Tetracyclines, chloramphenicol, and cotrimoxazole are commonly used medications to treat Salmonella infection in Ethiopia. 39 , 52 However, finding from this review indicated that Salmonella species were 93.30%, 78.26%, 63.64% resistant to tetracycline, chloramphenicol, and cotrimoxazole, respectively. These might be due to the overuse of these antibiotics in developing countries because of easy availability and low cost.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, irrationally prescriptions as empirical treatment options and over-the-counter use of these antibiotics are also common. 13 , 52 H influenzae was 100% resistant to meropenem. This will be challenged for future antibiotics therapy, since this drug is the last alternative for use when gram-negative bacteria are resistant to other commonly used antibiotics.…”
Section: Discussionmentioning
confidence: 99%